Towards a Capability-Based Decision Support System for a Manufacturing Shop - Barenji, Reza Vatankhah (Springer-Verlag Berlin, 2013)
To succeed, long term organizations must compete efficiently and out-perform their competitors in a dynamic environment. To survive in this competition, identification, classification and management of organizational capabilities are vital. This paper presents a methodology for developing a system to store, manage, and maintain intra-organizational capabilities for decision making processes on resources, processes and strategies for business opportunities. The proposed methodology is explored in an educational manufacturing cell.
14th IFIP WG 5.5 Working Conference on Virtual Enterprises (PROVE-VE) -- SEP 30-OCT 02, 2013 -- Dresden, GERMANY
Keywords: Capability; structural modeling; decision support system